Interactions between Kluyveromyces marxianus from cheese origin and the intestinal symbiont Bacteroides thetaiotaomicron: Impressive antioxidative effects. (August 2017) - Ceugniez, Alexandre; Tourret, Mélissa; Dussert, Elodie; Coucheney, Françoise; Deracinois, Barbara; Jacques, Philippe; Flahaut, Christophe; Heuson, Egon; Drider, Djamel; Behra-Miellet, Josette
Abstract: The effects of yeast Kluyveromyces marxianus S-2-05, of cheese origin, were assessed on the intestine anaerobe symbiont Bacteroides thetaiotaomicron ATCC 29741 to unveil any changes in its antioxidant properties. To this end, these microorganisms were grown and incubated either separately, or co-incubated, under anaerobic atmosphere. Afterwards, the microbial cells were recovered and washed, and extracts were prepared using a sterile detergent solution to mimic the intestine detergent content. The extracts prepared from K. marxianus S-2-05 and reference strain K. marxianus MUCL 29917, grown under different conditions, were assessed for their antioxidant properties against superoxide anion and hydrogen peroxide. Extracts from both yeasts showed antioxidative effects, which were particularly important for K. marxianus S-02-5 after anaerobic incubation. Moreover, K. marxianus S-02-5 displayed a high level of activity against the aforementioned reactive oxygen species, enhancing that of B. thetaiotaomicron ATCC 29741, after the co-incubation process. Two-dimensional polyacrylamide gel electrophoresis was used to separate the proteins extracted. Superoxide dismutase, thiol peroxidase, rubrerythrin -intensively produced by B. thetaiotaomicron induced by the yeast-were identified by mass spectrometry. The antioxidative potential evidenced for K. marxianus S-02-5 is another advantage which could justify the utilization of this strain as a probiotic for countering intestinal inflammatory processes. Highlights: An impressive antioxidant power of the yeast Kluyveromyce marxianus was found. Bacteroides thetaiotaomicron was used as a model of intestine bacterial anaerobe. The release of antioxidant compounds by this symbiont depends on its environment. Co-incubating both microorganisms benefited the bacterial population. Together, they produced more antioxidant extracts than did the single bacteria.